The prevalence of thyroid dysfunction and hyperprolactinemia in women with PCOS - van der Ham, Kim; Stekelenburg, Karlijn J.; Louwers, Yvonne V.; van Dorp, Wendy; Schreurs, Marco W. J.; van der Wal, Ronald; Steegers-Theunissen, Régine P. M.; Laven, Joop S. E. (Frontiers in Endocrinology, 2023)
Introduction: Ovulatory dysfunction is usually caused by an endocrine disorder, of which polycystic ovary syndrome (PCOS) is the most common cause. PCOS is usually associated with estrogen levels within the normal range and can be characterized by oligo-/anovulation resulting in decreased progesterone levels. It is suggested that decreased progesterone levels may lead to more autoimmune diseases in women with PCOS. In addition, it is often claimed that there is an association between hyperprolactinemia and PCOS. In this large well-phenotyped cohort of women with PCOS, we have studied the prevalence of thyroid dysfunction and hyperprolactinemia compared to controls, and compared this between the four PCOS phenotypes. Methods: This retrospective cross-sectional study contains data of 1429 women with PCOS and 299 women without PCOS. Main outcome measures included thyroid stimulating hormone (TSH), Free Thyroxine (FT4), and anti-thyroid peroxidase antibodies (TPOab) levels in serum, the prevalence of thyroid diseases and hyperprolactinemia. Results: The prevalence of thyroid disease in PCOS women was similar to that of controls (1.9% versus 2.7%; P = 0.39 for hypothyroidism and 0.5% versus 0%; P = 0.99 for hyperthyroidism). TSH levels were also similar (1.55 mIU/L versus 1.48 mIU/L; P = 0.54). FT4 levels were slightly elevated in the PCOS group, although within the normal range (18.1 pmol/L versus 17.7 pmol/L; P < 0.05). The prevalence of positive TPOab was similar in both groups (5.7% versus 8.7%; P = 0.12). The prevalence of hyperprolactinemia was similarly not increased in women with PCOS (1.3%% versus 3%; P = 0.05). In a subanalysis of 235 women with PCOS and 235 age-and BMI-matched controls, we found no differences in thyroid dysfunction or hyperprolactinemia. In according to differences between PCOS phenotypes, only the prevalence of subclinical hypothyroidism was significantly higher in phenotype B (6.3%, n = 6) compared to the other phenotypes. Conclusion: Women with PCOS do not suffer from thyroid dysfunction more often than controls. Also, the prevalence of positive TPOab, being a marker for future risk of thyroid pathology, was similar in both groups. Furthermore, the prevalence of hyperprolactinemia was similar in women with PCOS compared to controls.